Evaluasi Pembelajaran Berbasis Pendidikan Karakter di SMP Al Amin Sempu Secang - Yenny Aulia Rachman; Zaharah; Amiratul Munawaroh; Fatikhatul Muawanah; Hanif Hidayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The field of education is currently facing significant challenges, particularly concerning moral degradation. This research aims to understand the concept and analyze the results of the evaluation of Islamic Education (PAI) learning based on character education at SMP Al-Amin Sempu Secang, Magelang. This study employs field research with a qualitative approach. Data collection was carried out through observation, interviews, and documentation. The subjects of the study are students of SMP Al-Amin Sempu Secang, Magelang, while the object of the research is the character-building instruments, one of which is reflected in the exam questions designed by teachers to stimulate students to think positively. The findings of the research indicate that the evaluation of PAI learning at SMP Al-Amin integrates character development through exam questions. These questions are crafted to align with answers that leave a meaningful impression on students, encouraging them to internalize the implicit character values presented in the questions or answer options. At SMP Al-Amin, character development is also incorporated into Islamic Cultural History (SKI) exam questions, particularly in materials related to the Abbasid Caliphate. By implementing character-based evaluations in the PAI curriculum, holistic and integrated noble character traits are nurtured in students, enabling them to balance their character development effectively. Character education does not always need to be explicitly embedded within teaching materials during the learning process. Instead, through well-designed exam instruments, educators can convey messages of character education to their students. It is hoped that these messages will serve as life lessons (ibrah) that students can apply in their real lives.